INFLUENCE SIZE COMPANY, QUALITY AUDIT, GOOD CORPORATE GOVERNANCE AND LIQUIDITY TO OPINION AUDIT GOING CONCERN COMPANY GOODS CONSUMPTION REGISTERED IN BEI YEAR 2019-2021 - Enda Noviyanti Simorangkir; Darwin Wijaya; Felixcyrus Ganily; Angelina (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Company size, audit quality, good company leadership, and liquidity influence reception opinion auditing, which becomes attention. In market capital, this registered good company, big and small companies. Large and small companies alike have assets. A big company usually owns more Lot access than a small company. Large companies often get audit opinion concerns Because of the ease of obtaining funds. This research aims to evaluate the influence of company size, audit quality, good company management, and liquidity on a worrying audit opinion from a consumer goods company registered on the IDX between 2019-2021. Financial report data is the data source used in this research. This research analyzes Consumer Goods Companies Listed on the IDX 2019-2021. During the 2019–2021 research period, the sample selection technique was purposively used for choosing 61 companies. Results show that Opinion Auditing Going Concern Consumer Goods companies registered on BEI 2019-2021 are not influenced by the size of the Company, Quality Auditing, Good Corporate Governance, And Liquidity. Analysis data was done with analysis regression logistics in SPSS.